Gestión de control de la cuenta por cobrar de Comercial Joselito del Cantón Baba período 2020 - 2021. - Aguirre Veloz, Figna Antonella (2022)
The control management of accounts receivable is of great importance for companies since through this it will be possible to plan, organize, direct and monitor the policies, procedures and practices applied in a company for the respective credit that is applied to clients in a company, given that if the correct control of these accounts is not carried out, it could harm the health of the commercial due to lack of liquidity. Where the control management of accounts receivable was analyzed since there is an increase in the past due portfolio due to non-compliance by customers when making their payments, since the company has not implemented collection policies that are of great benefit to the respective collection, as well as the non-performance or investigation of the state of the credit history of the clients in other companies in order to know if they can access the credit or not. Performing the analysis of financial ratios. It should be noted that the present case study was carried out using quantitative and descriptive methodology, applying observation and interview techniques, having favorable results for the preparation of this work.